Literature Study Of Islamic Microfinance Institutions : Future Research Topics And Directions - M. Indra Mulia Nasution; Andri Soemitra (Enrichment : Journal of Management, 2022)
This research is a literature study related to Islamic Microfinance Institutions. Quantitatively analyzing the literature in the form of research results from the last five years from 2016 to 2020 published in various publishers with the help of software to track as many as 150 articles based on ratings. This study uses a content analysis approach, to describe the research topic and the structure of the field, author, country, publisher journal and network mapping of research topics. The results of the study found that the country that publishes the most journals related to Islamic microfinance is Malaysia. There are several main topics in the research range, namely: Poverty alleviation, Waqf-based microfinance, Marketing & Fintech, Sustainability & Outreach, Maqashid Syariah and Risk Management & Governance. We also offer future research directions. First, related to efforts to identify innovative applications of Islamic microfinance schemes that shift their focus to sustainable development. Second, the issue of shariah compliance is less explored in shariah microfinance research. Third, the development of Information and Communication Technology develops a sharia microfinance model based on Sharia-based financial technology (fintech) to provide benefits for poor entrepreneurs with limited access to financial institutions. The results of this study can be used for future researchers and for policy makers to be used as material for discussion on the need for regulatory reform to increase the practical feasibility of Islamic microfinance as an institution for microeconomic transformation.